Effect of O2 increase on properties of vanadium oxide coatings. (2nd June 2016) - Zairi, A.; Ben Cheikh Larbi, A.; Iost, A.; Staia, M. H.
Abstract : The present research was carried out with the aim of studying the influence of oxygen concentration during processing on the properties of the VOx coatings deposited by cathodic magnetron sputtering on a stainless steel AISI 316L substrate. Mechanical and tribological properties were measured by nanoindentation and sliding wear tests respectively. Adhesion was evaluated by means of the scratch test. In order to determine the texture of the coatings, complementary characterization methods including X-ray diffraction in grazing incidence and Bragg Brentano configurations, as well as Ω scans, were performed. It was found that the texture of the crystalline coatings is strongly influenced by the amount of partial pressure of oxygen in the reactor atmosphere. The V2 O5 phase, with an orthorhombic symmetry, was produced in the coating, which had a pronounced texturing for the (001) plane, exhibiting the best values of hardness and Young modulus. It was shown that, as the oxygen concentration drops to <1 sccm, the mechanical and tribological characteristics, as well as the coating adhesion, tend to decrease considerably.